Discrimination of the amplitude modulation rate - Lemańska, J.; Sęk, A. P.; Skrodzka, E. B. (Archives of Acoustics, 2002)
This study examines the amplitude modulation rate discrimination for sinusoidal and noise carriers. It was shown that the discrimination of AM rates is a monotonically growing function of modulation rate. Higher values of the discrimination thresholds were observed for a narrowband carrier. It appears that in the case of a narrowband noise carrier, the spectral range of the noise envelope is similar to that of the modulation rates of the signal (up to 120 Hz). It results in a masking in the modulation rate domain and in a much higher threshold growth than that observed for a wideband noise carrier or a sinusoidal carrier. The results are consistent with the idea of the so-called second stage of filtering acting on the envelope of the acoustic signal. This hypothesis postulates the existence of a so-called modulation filter bank, (MFB), responsible for the frequency selectivity observed in the amplitude modulation rate domain. The existence of the MFB suggests that a certain form of the spectral analysis of any acoustic signal envelope may be performed in the auditory system after initial filtering in the auditory filter bank. A model of the modulation rate discrimination based either on the classical concept of the excitation patterns or on the modulation excitation patterns has not accounted for our experimental data. According to both the models, an increase in the frequency discrimination threshold versus modulation rate should be slower than that measured in the experiment.